Using the barriers and facilitators to linkage to HIV care to inform hepatitis C virus (HCV) linkage to care strategies for people released from prison: Findings from a systematic review. Issue 2 (11th December 2019) - Yanes‐Lane, Mercedes; Dussault, Camille; Linthwaite, Blake; Cox, Joseph; Klein, Marina B.; Sebastiani, Giada; Lebouché, Bertrand; Kronfli, Nadine
Abstract: Elimination of hepatitis C virus (HCV) among short‐term sentenced prison populations will require improved access to HCV care and specific strategies dedicated to linkage upon release. Prison‐based HCV care has lagged behind HIV care, but much can be learned from HIV studies. We performed a systematic review to identify individual‐, provider‐ and system‐level barriers and facilitators to linkage to HCV and HIV care among released inmates. We searched MEDLINE, Scopus, the Cochrane Central Register of Controlled Trials and Embase, and performed a grey literature search for English articles published up to November 2018. Two searches were conducted, one each for HCV and HIV; 323 and 684 unique articles were identified of which two and 27 studies were included, respectively. Facilitators to linkage to HCV care included social support, having an existing primary care provider, and receipt of methadone, whereas barriers included a perceived lack of healthcare information and a lack of specialized linkage to care programs. The principal facilitators to linkage to HIV care included social support, treatment for substance use and mental illness, the provision of education, case management, discharge planning and transportation assistance. Important barriers were unstable housing, age <30 years, HIV‐related stigma, poor providers' attitudes and the lack of post‐release reintegration assistance. While HCV care‐specific studies are needed, much can be learned from linkage to HIV care studies. Ultimately, a multi‐pronged approach, addressing several individual‐level social determinants of health, and key provider‐ and system‐level barriers may be an appropriate starting point for the development of HCV linkage to care strategies.